Computational illustration of reactions of Cr(CO)3(η6-Naphthalene) complex with C2X2 molecules (X = H, F, Cl) - Seyed Mahdi Mirtaheri; Reza Ghiasi; Mohsen Zeeb; Hossein Anaraki-Ardakani (Results in Chemistry)
In the current investigation, analysis of two possible reactions of Cr(CO)3(η6-Naphthalene) complex with C2X2 molecules (X = H, F, Cl) was reported at the M06-2X/6-311G (d,p) level of theory. The considered reactions were [2 + 4] Diels–Alder cycloaddition reactions of naphthalene ring of complex with C2X2 molecules and substitution of carbonyl ligand with C2X2 molecule. Energetic aspects of these reactions were explored. Molecular orbital analyses of the reactants and products were exemplified. Variations of the CC bond distance in reactants, transition states and products were specified. Computed thermodynamics and kinetic parameters of these reactions were stated. Replacing effect of hydrogens atoms of C2H2 molecule with deuterium on the rate constant of DA reaction was described.